Copper(i) complexes: intramolecular and intermolecular arene-c– h···π(quasi-chelate ring) interactions - Yeo, Chien Ing *; Zukerman-Schpector, Julio; Ferreira, M. A. B; Tiekink, Edward R. T. * (2017)
A series of bis(phosphane)copper(I) thiocarbamates, namely (Ph3P)2Cu[ROC(=S)N(H)Ph]Cl, were prepared in response to the promising biological properties exhibited by the related phosphanegold(I) analogues. The presence of an intramolecular N-H···Cl hydrogen bond in the title compounds, was found leading to the formation of a six-membered quasi-chelate ring, CuCl···HNCS. Following ring closure, unanticipated C–H···π(quasi-chelate ring) interactions were evidenced in one-third of related copper(I) complexes capable of forming similar quasi-chelate rings. Computational chemistry calculations revealed that these interactions when occurring intramolecularly, afforded energies of attraction approximating 3.5 kcal mol-1. In a subsequent review of analogous copper(I) complexes, intermolecular C–H…π(quasi-chelate) interactions imparted stabilisation to the crystal structures, leading to zero-, one-, two- and even threedimensional architectures.